Determination of moisture content and moisture content profiles in wood during drying by low-field nuclear magnetic resonance. Issue 15 (18th November 2017) - Xu, Kang; Lu, Jianxiong; Gao, Yulei; Wu, Yiqiang; Li, Xianjun
ABSTRACT: In this article, the low-field nuclear magnetic resonance was used to measure the moisture content (MC) and MC profiles in poplar wood during real-time drying. The T 2 distribution curve at each drying stage measured using the Carr–Purcell–Meiboom–Gill pulse sequence provided detailed information in the dynamic change of free water as well as bound water of the whole wood sample. In addition, a new developed SE-SPI pulse sequence was first used to evaluate the spatially resolved T 2 distribution of the successive nondestructive sliced layer of wood. Combined with the area integration method, the moisture content in each layer was calculated, and the change of MC profiles within wood at the MC above and below fiber saturation point was well reflected.